Akulturasi Agama Dan Budaya Pada Perayaan Mandi Safar Adat Misool Kampung Lilinta Distrik Misool Barat Kabupaten Raja Ampat - Rusli, Rusdayati (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
This research was conducted using qualitative data types, the research location was Kampung Lilinta, West Misool District, Raja Ampat Regency, while the time of this research was carried out for about 1 month. With data collection techniques are observation, interviews, and documentation. The data obtained was obtained from several informants including traditional shops, religious shops, and local community shops. The results of the research on religious and cultural acculturation at the Misool Traditional Safar Bath Celebration in Lilinta Village, West Misool District, Raja Ampat Regency is a ritual process carried out in the Safar month on Wednesday in the last week of the Safar month which is believed to avoid bad luck that occurs during the Safar month. . During the safar celebration, the community is required to drink and bathe in water which has been prayed for by the religious shop, and on that day all activities are carried out outside the home until the reading of the prayer for safety led by the religious shop. This tradition aims to strengthen ties between the people of Lilinta Village, West Misool District, Raja Ampat Regency.